Accidente cerebravascular isquemico agudo en un paciente con tuberculosis diseminada - Rachid Bouchentouf (Sociedade Galega de Medicina Interna, 2000)
Miliary tuberculosis is a hematogenous dissemination of Mycobacterium Tuberculosis which involves especially lungs, central nervous system and lymph node. Stroke in tuberculous meningitis (TBM) occurs in 15-57% of patients especially in advance stage and severe illness. We report a 21-year-old man presented with rapid onset confusion and right hemiparesis. he had been recently diagnosed with miliary TB with central nervous system involvement. MRI of brain revealed acute ischemic stroke involving in left internal capsule. The outcome with antituberculosis treatment and corticosteroids was favorable.